Hello,

I’m brand to this site and I’m hoping that someone can show me the individual steps that allows the following equation:

t = P*R/S*E-0.6*P

Transpose to make P the subject per the following equation:

P = S*E*t/R+0.6t

Many Thanks,

Rich.

Printable View

- October 22nd 2012, 01:09 AMwardr1Steps to Transpose an Equation
Hello,

I’m brand to this site and I’m hoping that someone can show me the individual steps that allows the following equation:

t = P*R/S*E-0.6*P

Transpose to make P the subject per the following equation:

P = S*E*t/R+0.6t

Many Thanks,

Rich. - October 23rd 2012, 12:34 AMwardr1Re: Steps to Transpose an Equation
I've managed to figure this out by looking at similar posts (Sorry... I did say I was new!)

Anyway, here are the steps to transpose t = P*R/S*E-0.6*P making P the subject:

Attachment 25356

1. Multiply by (SE-0.6P)

Attachment 25357

2. Expand t(SE-0.6P)

Attachment 25358

3. Add +0.6Pt

Attachment 25359

4. Factorise PR+0.6Pt

Attachment 25360

5. Divide by R+0.6t

Attachment 25361

6. Rearrange P to L.H.S

Attachment 25362

If I've got this wrong, could someone let me know? - October 23rd 2012, 09:35 AMWilmerRe: Steps to Transpose an Equation
If that the case (denominator as you show) then

your equation requires brackets: t = P*R / (S*E-0.6*P) ; understand?

Crossmultiply:

PR = tSE - .6tP

Add .6tP to each side:

PR + .6tP = tSE

Factor left side:

P(R + .6t) = tSE

Divide each side by R + .6t:

P = tSE / (R + .6t) : notice brackets to CLARIFY denominator!

That's it.

Usually with these, you'd be expected to change .6 to 3/5, thus 3t / 5; so:

P = tSE / (R + 3t/5)

P = tSE / [(5R + 3t) / 5]

P = 5tSE / (5R + 3t)

Capish? - October 23rd 2012, 10:52 AMwardr1Re: Steps to Transpose an Equation
Got it,

Thanks for (Clarifying) that for me!